Rapid acquisition of microorganisms and microbial genes can help explain punctuated evolution - Rosenberg, Eugene (Frontiers in Ecology and Evolution, 2022)
The punctuated mode of evolution posits that evolution occurs in rare bursts of rapid evolutionary change followed by long periods of genetic stability (stasis). The accepted cause for the rapid changes in punctuated evolution is special ecological circumstances – selection forces brought about by changes in the environment. This article presents a complementary explanation for punctuated evolution by the rapid formation of genetic variants in animals and plants by the acquisition of microorganisms from the environment into microbiomes and microbial genes into host genomes by horizontal gene transfer. Several examples of major evolutionary events driven by microorganisms are discussed, including the formation of the first eukaryotic cell, the ability of some animals to digest cellulose and other plant cell-wall complex polysaccharides, dynamics of root system architecture, and the formation of placental mammals. These changes by cooperation were quantum leaps in the evolutionary development of complex bilolgical systems and can contribute to an understanding of the mechanisms underlying punctuated evolution.